Effect of coating on fiber laser welded joints of DP980 steels. (15th January 2016) - Cui, Q.L.; Parkes, D.; Westerbaan, D.; Nayak, S.S.; Zhou, Y.; Liu, D.; Goodwin, F.; Bhole, S.; Chen, D.L.
Abstract: Advanced high strength steels (AHSS), specifically dual phase (DP) steels, are extensively used to reduce the weight of vehicles. Fiber laser welding (FLW) has been shown to provide welds with superior mechanical properties made at high welding speeds. Galvannealing (GA) and galvanizing (GI) coated sheet steels are extensively used for auto bodies to improve corrosion resistance. As such, the effect of coating type on the microstructure, mechanical properties and fatigue properties of FLW similar joints of DP980 was assessed. There existed spherical tempered martensite in the GA coated DP980 base metal (BM), most likely caused by the galvannealing process. Coating type did not present a noticeable effect on the microstructure of the welded zones. The GI coating, however, could evaporate violently during welding, resulting in high concavity and other welding defects which negatively affect the high-cycle fatigue property. Measures to mitigate the negative effects of the GI coating were discussed. Graphical abstract: Highlights: Coating type has no effects on the microstructure in weld zones. GA steel welded joints showed improved mechanical properties due to lower concavity. Stage II fatigue crack growth took place in the fusion zone and heat affected zone interface.